2006
DOI: 10.1073/pnas.0600001103
|View full text |Cite
|
Sign up to set email alerts
|

Activity of dual SRC-ABL inhibitors highlights the role of BCR/ABL kinase dynamics in drug resistance

Abstract: Mutation in the ABL kinase domain is the principal mechanism of imatinib resistance in patients with chronic myelogenous leukemia. Many mutations favor active kinase conformations that preclude imatinib binding. Because the active forms of ABL and SRC resemble one another, we tested two dual SRC-ABL kinase inhibitors, AP23464 and PD166326, against 58 imatinib-resistant (IM R ) BCR͞ABL kinase variants. Both compounds potently inhibit most IM R variants, and in vitro drug selection demonstrates that active (AP23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 38 publications
1
86
0
Order By: Relevance
“…PD166326 is a nanomolar pyridopyrimidine inhibitor of ABL kinase effective against resistant BCR-ABL mutants. Conversely to imatinib, PD166326 also inhibits Src kinases and as such may exert additional effects on CML cell lines (38,39). IM-R and PD-R cells exhibited a drastic decrease in imatinib and PD166326 sensitivity as shown by cell metabolism and caspase assays.…”
Section: Discussionmentioning
confidence: 99%
“…PD166326 is a nanomolar pyridopyrimidine inhibitor of ABL kinase effective against resistant BCR-ABL mutants. Conversely to imatinib, PD166326 also inhibits Src kinases and as such may exert additional effects on CML cell lines (38,39). IM-R and PD-R cells exhibited a drastic decrease in imatinib and PD166326 sensitivity as shown by cell metabolism and caspase assays.…”
Section: Discussionmentioning
confidence: 99%
“…With over 500 kinases in the human genome (3), specificity is hard to achieve (11), and new molecules are needed as resistance mutants appear (8,79). Imatinib, nilotinib, and other "type II" inhibitors act by stabilizing the inactive DFG-out conformation, seen in eight kinases so far (16,80) and, which probably exists in many others.…”
Section: Src/abl-binding Free Energy Difference Measures the Conformamentioning
confidence: 99%
“…In Src and many other kinases, it is known that the DFG-out conformation is less stable than DFG-in, and this can explain at least part of the Src/Abl specificity of type II inhibitors like imatinib (33). Similarly, resistance screens have identified amino acids in Abl that reduce the effectiveness of imatinib and whose structure differs in the DFG-out and DFG-in states; they were postulated to act by destabilizing the DFG-out state, increasing ⌬G ii (8,33,37,38,79). However, no direct experimental proof or quantitative measurement of ⌬G ii has been obtained for any kinase.…”
Section: Src/abl-binding Free Energy Difference Measures the Conformamentioning
confidence: 99%
“…One can readily determine when mutations occur on a single DNA strand because they will appear on the same polony. Indeed, the simultaneous occurrence of multiple cooperating mutations in the same protein has been observed following in vitro mutagenesis and selection (Azam et al, 2006) and is beginning to be observed in clinical practice . Polony technology also allows for the quantification of BCR-ABL to ABL ratio and mutation haplotyping (Supplementary Figure), another example of its versatility.…”
Section: Discussionmentioning
confidence: 99%